The Weatherman from Greenwich: A new book ‘about’ Charles Todd - Campbell, Leith H (Journal of Telecommunications and the Digital Economy, 2018)
A new book, The Weatherman from Greenwich: Charles Todd – 1826 to 1910, promises to be a biography of Charles Todd, telecommunications pioneer in Australia. The title is, however, misleading. Most of the book is devoted to social influences in England and South Australia that may have shaped Todd’s early life. Todd’s early technical experience in England and his first activities in Australia are briefly sketched. Readers seeking a fuller account of Todd’s life and achievements should look elsewhere.